Integrasi Nilai-Nilai Hukum Islam dalam Pendidikan Kewarganegaraan: Telaah atas Pemikiran al-Farabi dan Ibnu Khaldun - Ikhwanudin, Ikhwanudin (Tasyri' : Journal of Islamic Law, 2025)
Abstract Civic Education (PKn) is often trapped in a normative narrative that is less relevant to Islamic legal values as the basis of social morality. This article examines the integration of Islamic legal values in the PKn through the analysis of the thoughts of Al-Farabi and Ibn Khaldun, two figures who offer distinctive views on ethics, social solidarity, and governance. This research aims to identify the concepts of justice, equality, and social harmony in the works of the two, as well as how these values can enrich the PKn curriculum in Islamic universities. Using a literature approach with a critical analysis of the main works of the two figures, this article finds that the integration of Islamic legal values is not only relevant, but also urgent to create a generation of students with a global perspective without losing their spiritual roots. In conclusion, Al-Farabi and Ibn Khaldun offer a solid theoretical foundation to reform the PKn to be more grounded and transformative.